FABRICATION OF PLGA NANOPARTICLE USING DOUBLE EMULSION SOLVENT EVAPORATION TECHNIQUE AS shRNA YB1 CARRIER - HARUN ISMAIL, AHMAD FAHMI; CHE ARIFFIN, SITI ’AISYAH; MOHD AFFANDI, NUR KHAIRUNISA (International Journal of Allied Health Sciences, 2020)
Colorectal cancer was reported to be the second cause of death among cancer patients for over 500,000 mortalities annually, as described by World Health Organization in 2018. This intense statistic was resulted from the unavailable treatment that specifically targeting a molecule that comprehensively dysregulate cancer cell growth, survival and metastasis. A multitasking protein namely Y-box-binding protein 1 (YB1) was found to be upregulated and directly contributed in nine of the Hanahan and Weinberg "Hallmark of cancer". Silencing this YB1 protein by any means including the use of short-hairpin RNA (shRNA) could embrace positive therapeutic consequences towards colorectal cancer patient. Despite the discovery of the YB1 multifunctional effect two years ago, limited research article was found to evaluate the effect of using nanoparticle delivery with shRNA YB1 encapsulated towards colorectal cancer cell. Therefore, an in-vitro investigation was conducted to explore the anti-proliferative effect of shRNA YB1 towards colorectal cancer cell lines (HT29) by using double emulsion solvent evaporation technique to fabricate PLGA nanoparticle as the shRNA carrier agent. In this study, the amplification of the shRNA YB1 was done in JM109 E.coli before it was extracted and encapsulated into PLGA nanoparticle. The validation of the anti-YB1 plasmid presence was validated through 1% agarose gel electrophoresis. The nanoparticle embedded with shRNA YB1 plasmid was fabricated through double emulsion solvent evaporation method. The resulted size, charge and morphology were observed and recorded. The effect of the YB1 gene silencing towards HT-29 cell proliferation was analyzed using MTT assay. The result reveals the presence of the shRNA YB1 plasmid by resulting approximately 2900 base pair of the shRNA. The size of the shRNA YB1 encapsulated nanoparticle was 345 nm with -26.1 mV charge. As for the HT29 treatment, it was indicated that the usage of shRNA YB1 loaded nanoparticle for 48 hours could reduce the cell viability (p<0.05) of the HT29.